Tourists’ Service Satisfaction of the Selected Amusement Parks in Subic Bay Freeport Zone - Abrajano, Rhia May C.; Fernandez, Grace; Salazar, Glenn (Future Science / FSH-PH Publications, 2023)
This descriptive-survey research determined the tourists’ service satisfaction of the selected amusement parks in Subic Bay Freeport Zone, Olongapo City. A total of 90 respondents served as the participants of the study. The researchers assessed the levels of satisfaction of amusement parks guests based on their perceptions. Guests were asked on how they can describe their satisfaction levels based on entertainments offered by the parks, staffs, safety and security, and cleanliness of each park. Entertainment wise, Amusement Park C was perceived by its guests as the most entertaining parks among the selected the amusement parks in the Freeport. Its adventurous and thrilling activities and wide vast forest area makes it more entertaining. The staffs of the Amusement Park A were given the highest rating by its guests compared to other selected amusement parks in the Freeport. Their staffs were considered by most of its guests as accommodating, informative and are always ready to serve the guests with all their requests. Safety and security were highly prioritized by the Amusement Park B management and it was confirmed by its guests based on their perception. This research find out that Amusement Park B and all its parks inside its area were considered by its guests as safe and secured as compared to its competitors in the Freeport. Few machines and technical rides inside the Amusement Park B made it safer for its guests. It was able to fully maximize nature for tourism and entertainment purposes. The highest rating for cleanliness, one of the several important factors that affects the levels of satisfaction of the guests, was given by the respondents to Amusement Park B. This gave the said amusement park the highest overall rating. The study recommends to conduct benchmarking or comparative studies of Freeport amusement parks with other amusement parks in the country. This shall focus on enhancing the tourism industry in the Freeport by learning new ways to make its tourism industry a truly world class.